(untitled) (Fiep Bulletin - online, 2016)
The contextualization is a dimension of pedagogical practice already addressed in physical education for some time. Think about other forms of thematizing the contextualization are needed to effectively assign meaning classes of physical education curricular component. In this study, is defined as contextual principles: knowledge of experience; respect for the cultural context; the epistemological curiosity; the recognition of everyday life; enhance the knowledge of students; and collective production of new knowledge. The intention is to analyze the contextualization of teaching in physical education classes of four high-school level teachers of State schools of Ceara in the municipality of Caucaia. The methodological approach used for the development of this research was the qualitative approach. The feature of this research is descriptive and exploratory. The study scenario was the municipality of Caucaia, part of the first Regional Coordination of the development of education, the Ministry of Education of the State of Ceará. Four teachers were selected for a deepening of this study. The field journal and observation records were necessary to give meaning to the experience. Realize that this comprehensive form contextualization already occurs in the physical education classes. In at least one class each teacher left to contextualize the subject. On the other hand, there is another professor who developed an entire class anchored in contextualization. Contextual principles help to better understand the benefits of contextualization if well applied. The closing of the study is to recognize that the contextualization already occurs in the physical education classes, could be better exploited, but the training has not favored for that sense. Teachers recognize and value the knowledge of students, knowing from experience, I look at the daily life and culture of the students, promote the epistemological curiosity. Missed only promote a useful knowledge and critical to the students reality.